2012
DOI: 10.1007/s11011-012-9365-z
|View full text |Cite
|
Sign up to set email alerts
|

Muscle depletion increases the risk of overt and minimal hepatic encephalopathy: results of a prospective study

Abstract: Muscle depletion is frequently encountered in cirrhotic patients. As muscle may represents an alternative site of ammonia detoxification in liver diseases, our study was aimed at investigating whether a decrease in muscle mass or function may independently influence the prevalence of neurocognitive alterations in cirrhosis. Three-hundred consecutive hospitalized cirrhotic patients were prospectively enrolled. Liver function, a complete neurocognitive assessment for the diagnosis of clinical or subclinical hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
171
4
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 211 publications
(189 citation statements)
references
References 13 publications
9
171
4
5
Order By: Relevance
“…59 Some subgroups of patients would benefit the most from testing for MHE as quite specific recommendations can be made if it is diagnosed. 3 Active drivers should be advised that they have diminished driving abilities and an increased probability of road traffic accidents; active workers ought to have their risk at work evaluated and counselling regarding handling complex/dangerous machinery should be provided; patients with cognitive impairment and decline in work performance perceived by themselves, relatives or by colleagues should be assessed and, if possible, changes in daily/working activities should be carried out.…”
Section: Discussionmentioning
confidence: 99%
“…59 Some subgroups of patients would benefit the most from testing for MHE as quite specific recommendations can be made if it is diagnosed. 3 Active drivers should be advised that they have diminished driving abilities and an increased probability of road traffic accidents; active workers ought to have their risk at work evaluated and counselling regarding handling complex/dangerous machinery should be provided; patients with cognitive impairment and decline in work performance perceived by themselves, relatives or by colleagues should be assessed and, if possible, changes in daily/working activities should be carried out.…”
Section: Discussionmentioning
confidence: 99%
“…83 For example, a recent prospective study demonstrated that cirrhotic patients with muscle depletion are at higher risk of HE and that the amelioration of nutritional status is an effective goal to decrease the prevalence of cognitive impairment in these patients. 84 As mentioned above, cirrhosis is often associated with thiamine (vitamin B 1 ) deficiency leading to increased prevalence of Wernicke's encephalopathy, a finding that has been attributed to loss of liver stores of thiamine. 85 In addition, cirrhosis is characterized by an imbalance in plasma levels of aromatic amino acids (AAAs) and branched-chain amino acids (BCAAs) and it has been suggested that altered plasma and brain BCAA/AAA ratios are implicated in the pathogenesis of HE in cirrhosis.…”
Section: Nutrition and The Central Nervous System Complications Of CImentioning
confidence: 99%
“…Similarly, poor nutritional status is common among cirrhotic patients, especially in advanced disease, and can be a compounding factor in the development of HE. In particular, the loss of skeletal muscle mass can lead to HE as skeletal muscle is involved in the metabolism of ammonia (table 2) [23]. …”
Section: Treatment Of Mhementioning
confidence: 99%